Ecotourism: An alternative of socio-ecological crisis?. (March 2019) - Syam, M; Aprillia, T; Maulana, I
Abstract: Wakatobi's natural landscape, well-known as "a real paradise under the sea", becomes one strategic area of the national tourism (KSPN). Wakatobi's ecotourism is based on the principle of sustainability. However, Wakatobi ecotourism does not meet ideal expectations. On the one hand, ecotourism is considered a way to avoid an environmental crises and to increase local economic growth. On the other hand, the development of Wakatobi ecotourism has resulted in marginalization and created a new social-ecological crisis. Access and opportunities of local peoples must be reviewed with the presence of the Tourism Authority Agency (BOP) as the protective body of the KSPN. BOP has become a new authority in the midst of overlapping authorities of Wakatobi National Park (TNW), Wakatobi District Government, and the customary authority. The customary authority as a public authority can at least be a "signpost" in the midst of state authorities (TNW, District Government & BOP), struggling to benefit from the nature of Wakatobi. Nevertheless, the paternalistic pattern of indigenous peoples also presents disputes in their institutions. Bajau ethnic, known as "orang laut", is always subordinated by "orang darat".